Chemical sphincterotomy in posthemorrhoidectomy pain relief: a meta-analysis - Yifan Cheng; Misha Mao; Yaqian Shang; Chaomei Ying; Linnan Guo; Yong Lu (BMC Surgery, 2023)
Abstract Purpose This study aims to evaluate the pain relief function of chemical sphincterotomy in patients undergoing haemorrhoid surgery and compare, through a meta-analysis, the different drugs used to treat this condition. Methods We conducted a search in databases including PubMed, EMBASE and Web of Science. The methodological quality was evaluated using the Revised Cochrane risk-of-bias tool for randomized trials (ROB2). The pain score was assessed using a visual analogue scale (VAS) on day 1, day 2, and day 7, and a meta-analysis was conducted based on the use of random effects models. In addition, the subgroup analysis was evaluated based on the kind of experimental drugs. Heterogeneity and publication bias were assessed. Results Fourteen studies with a total of 681 patients were included in this meta-analysis, and all studies were randomized controlled trials RCTs. Chemical sphincterotomy showed better pain relief function than placebo on day 1 (SMD: 1.16, 95% CI 0.52 to 1.80), day 2 (SMD: 2.12, 95% CI 1.37 to 2.87) and day 7 (SMD: 1.97, 95% CI 1.17 to 2.77) after surgery. In the subgroup meta-analysis, we found that different drugs for chemical sphincterotomy provided different pain relief. Conclusion Chemical sphincterotomy effectively relieves pain after haemorrhoidectomy, and calcium channel blockers have the best effect.